Decreased mitochondrial respiration in aneurysmal aortas of Fibulin-4 mutant mice is linked to PGC1A regulation. Issue 13 (21st June 2018) - van der Pluijm, Ingrid; Burger, Joyce; van Heijningen, Paula M; IJpma, Arne; van Vliet, Nicole; Milanese, Chiara; Schoonderwoerd, Kees; Sluiter, Willem; Ringuette, Lea-Jeanne; Dekkers, Dirk H W; Que, Ivo; Kaijzel, Erik L; et al.
Abstract: Aim: Thoracic aortic aneurysms are a life-threatening condition often diagnosed too late. To discover novel robust biomarkers, we aimed to better understand the molecular mechanisms underlying aneurysm formation. Methods and results: In Fibulin-4 R/R mice, the extracellular matrix protein Fibulin-4 is 4-fold reduced, resulting in progressive ascending aneurysm formation and early death around 3 months of age. We performed proteomics and genomics studies on Fibulin-4 R/R mouse aortas. Intriguingly, we observed alterations in mitochondrial protein composition in Fibulin-4 R/R aortas. Consistently, functional studies in Fibulin-4 R/R vascular smooth muscle cells (VSMCs) revealed lower oxygen consumption rates, but increased acidification rates. Yet, mitochondria in Fibulin-4 R/R VSMCs showed no aberrant cytoplasmic localization. We found similar reduced mitochondrial respiration in Tgfbr-1 M318R/+ VSMCs, a mouse model for Loeys-Dietz syndrome (LDS). Interestingly, also human fibroblasts from Marfan (FBN1) and LDS (TGFBR2 and SMAD3) patients showed lower oxygen consumption. While individual mitochondrial Complexes I–V activities were unaltered in Fibulin-4 R/R heart and muscle, these tissues showed similar decreased oxygen consumption. Furthermore, aortas of aneurysmal Fibulin-4 R/R mice displayed increased reactive oxygen species (ROS) levels. Consistent with these findings, gene expression analyses revealed dysregulation of metabolic pathways. Accordingly, blood ketone levels of Fibulin-4 R/R mice were reduced and liver fatty acids were decreased, while liver glycogen was increased, indicating dysregulated metabolism at the organismal level. As predicted by gene expression analysis, the activity of PGC1α, a key regulator between mitochondrial function and organismal metabolism, was downregulated in Fibulin-4 R/R VSMCs. Increased TGFβ reduced PGC1α levels, indicating involvement of TGFβ signalling in PGC1α regulation. Activation of PGC1α restored the decreased oxygen consumption in Fibulin-4 R/R VSMCs and improved their reduced growth potential, emphasizing the importance of this key regulator. Conclusion: Our data indicate altered mitochondrial function and metabolic dysregulation, leading to increased ROS levels and altered energy production, as a novel mechanism, which may contribute to thoracic aortic aneurysm formation.